노인의 구강건강에 따른 영양섭취상태 비교: 2015년 국민건강영양조사 자료를 이용하여 - 장은혜(Eun Hye Jang); 황세연(Se Yeon Hwang); 김지혜(Jihye Kim); 김석중(Seok Joong Kim); 양윤정(Yoon Jung Yang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2021)
본 연구에서는 국민건강영양조사 자료 제6기 중 2015년 자료를 이용하여 우리나라 65세 이상 노인을 대상으로 구강건강수준과 영양상태와의 관련성에 대해 분석하였으며 주요 결과에 대한 요약은 다음과 같다. 가구소득이 낮을수록 본인인지 구강건강상태가 나쁘다고 응답한 사람들이 많은 것으로 나타났으며, 연령이 많을수록, 교육수준이 낮을수록, 가구소득이 낮을수록 씹기 문제가 있다고 응답한 사람들이 많았고 연령이 많을수록, 교육수준과 소득이 낮을수록, 현재 흡연자일수록 말하기 문제가 있다고 응답한 사람들이 많은 것으로 나타났다. 씹기 문제가 있는 그룹에서 리보플라빈의 섭취량이 씹기 문제가 없는 그룹보다 낮았고, 리보플라빈 섭취 부족자의 비율이 높았다. 말하기 문제가 있다고 응답한 그룹에서 견과류 및 종실류의 섭취와 버섯류의 섭취량이 말하기 문제가 없다고 응답한 그룹에 비해 낮았고, 식이섬유의 섭취량도 말하기 문제가 있다고 응답한 그룹에서 낮았다. 또한 철 섭취가 부족한 사람의 비율도 말하기 문제가 있는 그룹이 없는 그룹보다 유의적으로 높았다. 이처럼 구강건강상태 중 특히 씹기 문제와 말하기 문제가 있는 노인은 식품 및 일부 영양소의 섭취가 낮은 것으로 나타나 노인의 구강건강상태가 영양상태와 밀접한 관련이 있음을 확인하였다. 따라서 구강건강상태를 향상시키기 위한 구강건강관리와 균형적 영양섭취에 대한 중재가 필요한 것으로 사료된다. This study examined the general characteristics and nutritional status by oral health among the Korean elderly. The data from the 2015 Korea National Health and Nutrition Examination Survey (KNHANES) were used. The subjects were 1,352 old adults aged 65 years old and older. The oral health indicators were classified after completing a questionnaire asking about the experiences of toothache within the recent year, self-perception of oral health, chewing difficulty, and speaking difficulty. The group with poor self-perception of oral health had lower household income. The group with chewing difficulty showed older age, lower education status, and lower household income. The group with speaking difficulty showed older age, lower education status, lower household income, and higher current smoking. The group with speaking difficulty showed lower intakes of nuts and seeds and mushrooms. The group with chewing difficulty had a lower riboflavin intake than those without chewing difficulty. The group with speaking difficulty showed a lower intake of dietary fiber than those without speaking difficulty. Compared to the Korean Dietary Reference Intakes (KDRIs), the group with chewing difficulty showed a higher proportion of insufficiency in riboflavin intake than those without chewing difficulty. The group with speaking difficulty showed a higher proportion of insufficiency in iron intake than those without speaking difficulty. These findings showed that the elderly with chewing and speaking difficulties have a low nutritional status in some nutrients. Therefore, nutritional intervention and oral health care are necessary. KCI Citation Count: 4